The rule of lead = La regola del piombo - Arrigoni, Giacomo; Cinque, Gledis; Continanza, Marco; Giacomo Arrigoni Productions; Leomark Studios (Firm) ([Milan, Italy] : Giacomo Arrigoni Productions, 2014)
Following otherworldly plans which he finds very annoying, Humphrey, the ghost of a murderer, is forced to team up with Lara, a lonely teenage girl ignored by parents and society. Unable to touch things and assume a human form that would lead to the ultimate demise of his soul, Humphrey must lead the girl to save two kidnapped children as a way to redeem himself and finally abandon Earth. The two make an unpredictable rough pair and explore the old mansion where some criminals are holding the children for their shady business. The ghost and the girl find the children and try to draw the attention of the city, but nobody listens to them: they're just invisible creatures trying to point out the existence of two invisible children. Unable to believe in himself and convinced that he is damned forever, Humphrey abandons the mission and vanishes, forcing Lara to act on her own to save the kids. But when the criminals kidnap Lara, Humphrey realizes that he must do his best to awaken the entire city and open the eyes of the people who continue to ignore the existence of the prisoners. Then, as he recalls what his alchemist father told him when he was a child, that even the most impure stone can be transformed into gold, Humphrey faces the most difficult choice of his afterlife: remaining damned forever or risking a final death by taking on human form to free the prisoners - a choice that can transform his soul from lead to gold.
Originally released as a motion picture in 2014.
Gledis Cinque, Marco Continanza, Antonio Carlucci.
Cinematographer, Davide Crippa ; editor, Giacomo Arrigoni ; music, Fabio Viana.
In Italian with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 8, 2016).
Keywords: Kidnapping victims -- Drama; Redemption -- Drama; Ghost stories, Italian; Ghost films; Fantasy films; Feature films; Internet videos; Streaming video